Explanation: x3x3x3=x3+3+3=x9 and x3×3×3=x33×3=x39=x93=x27
When multiplying a base with exponents by the same base with exponents, we add the exponents.
When raising a base to multiple exponents, we multiply exponents. In this example, the multiplication of exponents completely overcomes the adding exponents by an exponential factor, here by cubing the answer.
So we can recommend you notes for your school.
Please enter below the email address you registered with and we will send you a link to reset your password.
Get notes from the top students in your class.